Enhanced 3D terrain visualization process using game engine - Mohd Hafiz, Mahayudin (2018)
Recently, many information visualization regarding terrain use 2D maps which include shading and lines to show the terrain. However, the emerging 3D terrain visualization technologies and software may produce a lot of terrain information. This emerging technology is also concurrent with the growth of game engines. As for this study, Unity3D, one of these game engines, has built-in terrain engine that provides 3D terrain visualization. Moreover, this engine provides the ability to be able to publish as web application for the online environment. Based on the literature review, there are studies related to terrain visualization developed using game engines, however, majority focuses on the capability of terrain visualization in an offline environment. None of these studies focus on the performance of the 3D visualization process in an online environment. Thus, the aim of this study is to enhance the process of generating 3D terrain visualization with GIS data generated from the Unity3D game engine in an online environment. The results of the performance are compared with two different situation that is online and offline. Several experiments are conducted and performances are measured based on loading time, response time, frames per second (FPS), memory usage and CPU usage of different terrain data types and size. The study adopts design research process that is comprised of problem identification from literature review, solution development by using the process to develop the prototype needed, and evaluation by comparing the output of the visualization process. The findings show that the process of enhancing 3D terrain visualization with GIS data generated from the Unity3D game engine in offline environment is better compared to those online. This is due to the compression and the need for Unity3D web player to make contact with the Unity server for authentication and also for visualization during online. Furthermore, operating system resource needs to be used before it goes online. The main finding of this study is the new algorithm of enhancing 3D terrain visualization process using Unity3D game engine. The algorithm can be divided into three processes which are terrain data reading, terrain data conversion, and terrain data processing. It may assist the developer on how to enhance the process of developing web-based 3D terrain visualization using Unity3D game engine.